Bag valve resuscitator versus Mapleson C circuit during manual ventilation: A bench top study. (June 2022) - Giani, Marco; Lucchini, Alberto; Moretto, Lorenza; Di Pierro, Michela; Lo Re, Fabio; Mancini, Paolo Giobbi; Palano, Salvatore; Foti, Giuseppe; Bellani, Giacomo; Bronco, Alfio
Abstract: Background: Manual ventilation is life saving in critically ill patients. The lack of airway pressure monitoring makes it operator and device dependent. In this bench top-study, we compared a self- inflating bag valve resuscitator and a Mapleson C circuit during manual ventilation performed by critical care nurses under normal and pathologic conditions, with a special focus on delivered positive end expiratory pressure (PEEP). Methods: Three different respiratory patterns (normal, restrictive and obstructive) were reproduced by a breathing simulator. Twenty nurses provided manual ventilation with a specific ventilatory pattern. Airway pressure, tidal volume and respiratory rate were recorded. Absolute value, error (difference between recorded and target values) and variability of PEEP were analysed. Results: 3820 breathing traces were analysed. PEEP error was significantly higher with Mapelson C (43.3% vs 5.9% respectively, p < 0.001). This finding was confirmed regardless of operator skill and scenario. PEEP was more variable with Mapelson C (p < 0.05 in all scenarios). Ventilation of obstructive patients with Mapelson C resulted in higher PEEP levels compared to the reference value. Conversely, in the restrictive setting, PEEP was lower. Difference between PEEP and the minimum pressure recorded during the respiratory cycle was significantly higher with Mapelson C (p < 0.05). Conclusions: Manual ventilation with a Mapleson C circuit delivered a less accurate and less stable PEEP level compared to a self-inflating bag valve resuscitator.